2015
DOI: 10.1007/s00221-015-4372-z
|View full text |Cite
|
Sign up to set email alerts
|

Memory load effect in auditory–verbal short-term memory task: EEG fractal and spectral analysis

Abstract: The objective of this preliminary study was to quantify changes in complexity of EEG using fractal dimension (FD) alongside linear methods of spectral power, event-related spectral perturbations, coherence, and source localization of EEG generators for theta (4-7 Hz), alpha (8-12 Hz), and beta (13-23 Hz) frequency bands due to a memory load effect in an auditory-verbal short-term memory (AVSTM) task for words. We examined 20 healthy individuals using the Sternberg's paradigm with increasing memory load (three,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 79 publications
0
14
1
Order By: Relevance
“…Interestingly, a wide range of recent studies report the involvement of beta oscillations in WM processes (Deiber et al ., ; Axmacher et al ., ; Siegel et al ., ; Johnson et al ., ; Spitzer & Haegens, ), although its specific role is still unclear. Increased beta activity during WM maintenance has been reported for WM tasks of different modalities: visual (Tallon‐Baudry et al ., , ), tactile (Spitzer et al ., ), auditory (Stokić et al ., ; Yu et al ., ) and temporal (Chen & Huang, ). Moreover, beta power increases with memory load (Leiberg et al ., ; Deiber et al ., ; Palva et al ., ; Honkanen et al ., ; Chen & Huang, ; Kornblith et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, a wide range of recent studies report the involvement of beta oscillations in WM processes (Deiber et al ., ; Axmacher et al ., ; Siegel et al ., ; Johnson et al ., ; Spitzer & Haegens, ), although its specific role is still unclear. Increased beta activity during WM maintenance has been reported for WM tasks of different modalities: visual (Tallon‐Baudry et al ., , ), tactile (Spitzer et al ., ), auditory (Stokić et al ., ; Yu et al ., ) and temporal (Chen & Huang, ). Moreover, beta power increases with memory load (Leiberg et al ., ; Deiber et al ., ; Palva et al ., ; Honkanen et al ., ; Chen & Huang, ; Kornblith et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that EEG sources with theta and alpha band activities are associated with workingmemory tasks (Debener et al 2005;Khader et al 2010;Dong et al 2015;Stoki et al 2015;Esposito et al 2009), therefore, both sensor and source-level EEGs were band-pass filtered to theta and alpha bands. Next, the EEGs were Hilbert enveloped, convolved with a canonical HRF (Glover 1999), and downsampled to the frequency of the fMRI recording (0.4545 Hz).…”
Section: Data Preprocessingmentioning
confidence: 99%
“…There is a study that applies complexity estimation to the assessment of the activity of the short-term memory [5]. This study shows that with the increase in memory load, fractal dimension value decreases in frontal region and increases in temporal regions and parietal regions.…”
Section: Introductionmentioning
confidence: 97%
“…As a result, fractal dimension analysis can reflect the activity of the working memory better than sample entropy analysis. Moreover, in order to investigate the relationship between the fractal dimension value and the power of theta band (4)(5)(6)(7)(8) in the frontal region, we conducted a correlation coefficient analysis. The result showed that increase of the power of theta band and decrease of fractal dimension value has relatively high correlation.…”
mentioning
confidence: 99%